HOUSING PLANNING WITH A SCANDINAVIAN CONTEMPORARY ARCHITECTURE APPROACH IN WONOSOBO - jatmiko; Hendriani, Adinda Septi (Clean Energy and Smart Technology, 2026)
To realize the concept of housing planning and design with a Scandinavian contemporary architectural approach as a clean, healthy, and cool residential area equipped with supporting facilities such as sports facilities, prayer rooms, gardens, which can provide a sense of comfort through processing the site plane layout based on architectural concepts so that it can give an impression to the building by applying appropriate forms. The Design Method is a system or strategy used to collect data in the form of information and ideas that can support the design. By analyzing the results of observation data and literature studies, so that potential and problems can be obtained that will be the basis for design. Analyze site conditions in the form of site utilities, sun orientation, wind direction, noise, achievement/accessibility, location and social conditions of the local community. From the results of comparative studies that have been carried out on four different buildings, students draw conclusions about how the concept of a Scandinavian contemporary house and what components are usually found in Scandinavian contemporary house buildings. From the three buildings, students will take several room criteria that will be used as considerations in planning Housing Planning With a Scandinavian Contemporary Architectural Approach in Wonosobo. The plan will include the construction of several housing clusters of various sizes. Natural lighting will be maximized so that the homes will reflect Scandinavian contemporary values.